Clinical and Prognostic Implications of P21 (WAF1/CIP1) Expression in Patients with Esophageal Cancer: A Systematic Review and Meta-Analysis. (7th January 2020) - Wu, Junbo; Liu, Liang; Wu, Feng; Qiu, Li; Luo, Ming; Ke, Qing; Deng, Xinzhou; Luo, Zhiguo
Abstract : Background . Previous studies have demonstrated that P21 (WAF1/CIP1) is a valuable prognostic factor in several malignant tumors. However, it is not known whether P21 can predict the prognosis in patients with esophageal cancer (EC). The aim of this research was to investigate the contribution of P21 expression to the clinicopathological characteristics and of EC. Methods . A systematic review and meta-analysis of study focusing on P21 expression, clinicopathological characteristics, and clinical outcomes in patients with EC was performed using seven databases (PubMed, Embase, Web of Science, and four Chinese databases). Pooled hazard ratios and odds ratios were used to explore the association between P21 expression, clinicopathological characteristics, and outcomes in patients with EC. The heterogeneity of the studies was classified by the I 2 statistic. The sensitivity analysis was then utilized to assess the robustness of the results. Finally, the funnel plot and Begg's test were used to evaluate the publication bias. Results . Forty-five studies with 3098 patients were eligible for inclusion in the meta-analysis. Thirty of these studies reported on clinicopathological characteristics and 15 on clinical outcomes. The pooled hazard ratio of 1.456 (95% confidence intervals 1.033–2.053, P = 0.032 ) for overall survival indicated that a low P21 expression level was an unfavorable prognostic factor for a clinical outcome in patients with EC. Furthermore, the pooled odds ratio confirmed an association between decreased P21 expression and poor clinicopathological characteristics, including differentiation, lymph node metastasis, invasion, and higher grade and clinical stage. Notably, high P21 expression was a significant predictor of a favorable response to chemotherapy. There was no evidence of publication bias. Conclusion . Reduced P21 expression is associated with a poor outcome in patients with EC.